Wound Integrity of 2.0 mm Transconjunctival Single-Plane Sclerocorneal Incision: A Comparison between a Motorized Injector with/without Pause Time and a Manual Injector - Hisanori Imai; Ayaka Fujii; Emiko Tani; Atsushi Azumi (Journal of Ophthalmology)
Purpose. To compare the final incision size and wound structure after the intraocular lens implantation from 2.0 mm transconjunctival single-plane sclerocorneal incision (TSSI) between the use of a motorized injector at first speed and the use of a manual injector. Methods. Patients were divided into three groups as follows: Group A, a manual injector, Group B, a motorized injector with 0.5 s pause time, and Group C, a motorized injector without pause time. The change in incision size and anterior segment optical coherence tomography findings of the wound structure were analyzed. Results. 110 eyes were enrolled (Group A: 40, Group B: 30, and Group C: 40). The averaged change in incision size (mm) was 0.08, 0.01, and 0.03 in Groups A, B, and C, respectively (p<0.001). The incision enlargement in Group A was statistically larger compared with other groups (p<0.01). Descemet’s membrane detachments were seen in 26, 9, and 27 eyes one day after the surgery in Groups A, B, and C, respectively (p=0.001). The rate of Descemet’s membrane detachment in Group B was significantly lower than other groups (p<0.01). Conclusions. The use of a motorized injector by fastest setting with 0.5 s pause time is the best for less wound damage in 2.0 mm TSSI.